Can Succinylcholine be Used Safely in Severely Burn Patients? - Begum, H; Islam, MS; Khatun, UHS (Journal of Bangladesh College of Physicians and Surgeons, 2012)
The use of succinylcholine(SC) in burn patients arerelatively contraindicated for certain period after lesion aged4 days 10 weeks due to chance of hyperkalemia althoughthere are no systemic data to define what period and whatlevel of K+ is safe. This prospective study was carried out in60 acute burn patients who were admitted in DMCH BurnUnit and undergone surgery within 3 months of lesion. Mostcommon type of burn was flame burn (33%).Mean age ofthe patient was 22.60 ± 9.61, TBSA (Total burn surface area)was 22.17 ± 9.57 and duration of burn was 23.36 ± 19.61.Every patient received standard dose of SC (1.5mg/kg) forintubation. The peripheral venous blood samples for serumK+, Na+, Cl - & HCO3- were drawn before induction and 3minutes after injection of SC. On analysis there were nosignificant change of serum K+ and HCO3- (p > .05), on theother hand serum Na+and Cl- levels were significantlychanged (p<0.05) due to correction of dehydration. In caseof electric burn serum K+ level was raised in every casesbut didnt cross the normal high level of serum K+ (5.5mEq/l). Haemodynamic parameters like pulse, NIBP, SPO2 andECG were analyzed intra operatively and there were nosignificant change in NIBP and ECG, rather there weresignificant improvement in pulse and SPO2 (p< 0.05).Survival of anaesthetic was 100% and no dysrhythmias ormajor morbidity were found intra operatively. Therefore,these data taken in the context of a compelling case forrapid intubating condition suggest safety in succinylcholineuse in the patients with acute burn. DOI: http://dx.doi.org/10.3329/jbcps.v30i1.11360 J Bangladesh Coll Phys Surg 2012; 30: 5-9